Pozycja oraz opinia biegłego w sądowej praktyce zawodowej w systemie prawnym anglosaskim i rosyjskim. Rys porównawczy - Goźdź-Roszkowski, Stanisław; Mazurkiewicz-Sułkowska, Julia (2022)
This paper approaches the position of expert witnesses and written expert opinions from a comparative perspective by considering such aspects as: qualifications required to become an expert witness, the way in which experts are appointed, the role and importance of expert opinion in court proceedings. The paper discusses the impact of legal provisions on the way(s) in which the opinions are expressed, especially the extent to which law imposes a fixed organizational format. It turns out that some fundamental differences between the position of expert opinions and their opinions result from the radically different legal systems and cultures. While the Russian legal system appears to codify nearly each aspect of the expert witness work and their opinion, experts in Anglo-American systems have much more leeway in shaping the conventions of the genre, as long as they take account of the general standards contained in the relevant legislation and case law.
Keywords: expert opinion; expert witness; legal discourse; institutional discourse